1997
DOI: 10.1002/anie.199708421
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Oligomerization of Ribonucleotides on Guanosine‐Rich Templates: Suppression of the Self‐Pairing of Guanosine

Abstract: COMMUNICATIONSpear to be generated at intermediate acidities; this phenomenon requires further investigation.Given the controversial nature of our findings, we decided to prepare 4 under our conditions (Scheme 2). Only modest yields (7.7 %) were obtainable, but this reaction is no doubt complicated by the presence of the third aldehyde grouping. 'HNMR data again only showed the presence of the expected resonances; the extra peaks noted by Berlin et al. were absent, even for spectra recorded at 500 MHz ( Figure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 33 publications
(1 reference statement)
3
36
0
Order By: Relevance
“…The failure of template reactions in systems where the B form of DNA is stable illustrates this point. [13,14,16] The results presented above reinforce the suggestion of Göbel and co-workers [13,14] that the work of Wu et al [2,5,6] may represent a somewhat too pessimistic view on the prospects for nonenzymatic replication of RNA. In many earlier experiments, as in those reported above, the primer consisted of an oligodeoxynucleotide terminated by a single ribonucleotide residue and the template was an oligodeoxynucleotide.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The failure of template reactions in systems where the B form of DNA is stable illustrates this point. [13,14,16] The results presented above reinforce the suggestion of Göbel and co-workers [13,14] that the work of Wu et al [2,5,6] may represent a somewhat too pessimistic view on the prospects for nonenzymatic replication of RNA. In many earlier experiments, as in those reported above, the primer consisted of an oligodeoxynucleotide terminated by a single ribonucleotide residue and the template was an oligodeoxynucleotide.…”
Section: Discussionsupporting
confidence: 90%
“…With this arrangement, the template ± primer double helix may not adopt an A conformation around the 3'-terminus of the primer. [13,14] Therefore, the primer extension reaction may be inhibited. Clearly, more detailed information transfer experiments with RNA primers and templates are now necessary, and they are underway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If poly(C) is incubated with an equimolar mixture of the four 2-MeImpNs (N ¼ G, A, C, or U), less than 1% of the product consists of noncomplementary nucleotides (Inoue and Orgel 1982). Subsequent experiments suggested that this and the related reactions discussed later occur preferentially within the context of double helices that have a structure resembling the A form of RNA (Kurz et al 1997(Kurz et al , 1998Kozlov et al 1999Kozlov et al , 2000.…”
Section: Nonenzymatic Replication Of Rnamentioning
confidence: 99%
“…There is now substantial evidence that the templatedirected oligomerization of 2-Me-imidazole derivatives proceeds best in double helices that adopt the A-form nucleic acid structure (Kurz et al, 1997(Kurz et al, , 1998Kozlov et al, 1999bKozlov et al, , 2000b. RNA sequences are superior to DNA sequences as templates, but the general features of the reactions are similar for RNA and DNA templates (Zielinski et al, 2000).…”
Section: Template-directed Synthesismentioning
confidence: 99%